Entre paisagens e urbanidades: a caracterização do corredor de urbanidade de Santa Maria, RS - Flores, Gabriela Martins (2024)
Landscape in this work can be understood as fundamental to addressing contemporary challenges in urban areas. In the midst of the urbanization scenario of cities, the so-called Urbanity Corridor emerges as a road structuring axis, an area that is the result of a restructuring process and the increase in intra-urban circulation that connects the decentralization of a city. Characterized by the encouragement of miscegenation, verticalization and densification of land use, this urban corridor directly interferes with the urban landscape, calling into question the relationship between built space and natural landscapes in shaping the urban landscape scenario. The aim is to characterize the landscape of Santa Maria's Urban Corridor, located in the center of the state of Rio Grande do Sul, as part of the municipal master plan. To do this, a literature review was carried out, reflecting on urban landscape, urbanity and corridors, in order to understand the concept of this type of corridor and how they can be analyzed. Next, examples of urban corridors in Brazil were spatialized, based on the cases of five Brazilian cities, using the multiscalar comparative method in order to understand the spatial-territorial characterization of this type of corridor in terms of physical and morphological aspects in the Brazilian territory. As for the object of study in the city of Santa Maria, the characterization and territorial legislative analysis was developed with thematic maps of the corridor's configuring elements, based on land use and occupation legislation and the master plan, biophysical attributes, demographic aspects and urbanization. The aim is to analyse and understand the characteristics of the Urbanity Corridor, developing a reading and diagnosis of its morphological patterns and spatial dynamics of the landscape, based on the spatialization of thematic maps, identifying homogeneous areas with similar aspects, divided into Landscape Units along its length in the city. In this way, it was possible to understand the landscape of the corridor from horizontal study planes, and it was necessary to complement this with studies from an observer's point of view. The methodology of urban landscape catalogs was thus implemented, bringing together, identifying and characterizing the landscape on a micro scale, in order to understand the main aspects of this typology and the relationships in the shaping and transformation of the landscape. The results culminated in the identification of an index to measure the urbanity of the landscape, thus verifying areas of greater or lesser urbanity in the study area. They made it possible to identify eight Landscape Visual Points along the central road axis, using thematic mapping procedures and photointerpretation of visibility planes to understand the urban landscape of the Urbanity Corridor in each of the landscape units, understanding the relationships between the corridor, urbanity and the city's landscape.